The Development of Interactive Learning Media Through Flipbooks in Creative Products and Entrepreneurship Subjects for Grade XI - Andri Lukmana; Syafaatul Hidayati (Pekobis : Jurnal Pendidikan, Ekonomi, dan Bisnis, 2024)
The purpose of this project work is to develop flipbook interactive learning media in the subject of creative products and entrepreneurship in class XI. This project work uses the Research and Development (R&D) method, with the development model in this project work research ADDIE. The subjects of this project work include material experts, media experts, linguists. The subjects of the small-scale trial were 5 participants and 25 students of the field trial of class XI TKJ 1 SMK Pustek Serpong. Data collection was carried out using questionnaires, observası and dokumentası. The data analysis technique uses quantitative descriptive analysis. The results of the research show that the development of flipbook interactive learning media in the subject of creative products and entrepreneurship in class XI is suitable for learning activities for students of class XI TKJ 1 SMK Pustek Serpong. The conclusion was drawn based on the results of the validation of material experts with 4.08, linguists with 4.2, media experts with a score of 5 and the average final assessment score of 4.42 with the category of very suitable for use.